Short-term efficacy and mechanism of semiconductor laser combined with local injection of glucocorticoids in treatment of erosive oral lichen planus - SUN Yinyin, LIU Siyu, XU Xiaoyu, LU Shulai (精准医学杂志)
Objective To investigate the short-term efficacy of semiconductor laser combined with local injection of glucocorticoids in the treatment of erosive oral lichen planus (EOLP) and its effect on the level of interleukin-18 (IL-18) in saliva. Methods A total of 90 patients who met the clinical and pathological diagnostic criteria for EOLP were randomly divided into groups A, B, and C, with 30 patients in each group. The patients in group A were treated with glucocorticoids, those in group B were treated with semiconductor laser, and those in group C were treated with semiconductor laser combined with glucocorticoids. The level of IL-18 in saliva was measured for all patients before treatment and at week 4 of treatment; the area of lesion and the degree of pain at the base of the lesion area were measured before treatment and at weeks 2 and 4 of treatment; clinical outcome was assessed at week 4 of treatment. Results After 4 weeks of treatment, all three groups had a significant reduction in the level of IL-18 in saliva (F=90.456-697.671,P<0.05), and group C had a significantly lower level of IL-18 in saliva than groups A and B (F=25.803,P<0.05). At weeks 2 and 4 of treatment, all three groups had a significant reduction in the area of lesion (F=-104.445-54.096,P<0.05). All three groups had a significant reduction in VAS score from before treatment to weeks 2 and 4 of treatment and from week 2 to week 4 of treatment (F=2.546-4.665,P<0.05). At week 4 of treatment, groups A and C had a significantly better clinical outcome than group B (H=7.561,23.262,P<0.05), and there was no significant difference between groups B and C (P>0.05). Conclusion Semiconductor laser combined with glucocorticoid therapy has a better clinical effect than each therapy alone in the treatment of EOLP, and it can significantly improve clinical symptoms within a short period of time, possibly by reducing the level of the inflammatory factor IL-18 in saliva.